Multiple peroxisome proliferator-activated receptor beta subtypes from Atlantic salmon (Salmo salar) - Leaver, Michael; Ezaz, M Tariq; Fontagne, Stephanie; Tocher, Douglas R; Boukouvala, Evridiki; Krey, Grigorios (Journal of Molecular Endocrinology, 2007)
Peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors belonging to the nuclear hormone receptor superfamily that function as critical regulators of lipid and energy homeostasis. Although intensively studied in mammals, their basic biological functions are still poorly understood. The objective of this work was to characterise PPARβ subtypes in a fish the Atlantic salmon (Salmo salar) in order to address PPAR function and the regulation of lipid homeostasis in lower vertebrates. The screening of an Atlantic salmon genomic library revealed the presence of four genes for PPARβ subtypes. Based on comparisons of exons and exon-flanking regions, these genes were assigned into two families, ssPPARβ1 and ssPPARβ2, each family containing two isotypes; ssPPARβ1A and β1B and ssPPARβ2A and β2B. Two full-length cDNAs for ssPPARβ1A and ssPPPARβ2A were isolated. Transcripts for ssPPARβ1A and ssPPARβ2A have distinct tissue expression profiles, with ssPPARβ1A predominating in liver and ssPPARβ2A predominating in gill. Expression levels of mRNA of either isotype were up to ten fold lower in kidney, heart, spleen, muscle, and brain. In cellular transfection assays ssPPARβ1A is activated by monounsaturated fatty acids, 2-bromopalmitate and by the mammalian PPARβ-specific ligand GW501516. In contrast, PPARβ2A was not activated by any of the compounds tested. Furthermore, ssPPARβ2A repressed both basal reporter gene activity and the GW501516-induced activity of ssPPARβ1A. The results indicate unexpected levels of variety and complexity in PPAR subtype and mechanism of action in lower vertebrates.